Facile aqueous synthesis and stabilization of nearly monodispersed gold nanospheres by poly(L‐proline). Issue 6 (7th January 2013) - Gkikas, Manos; Timonen, Jaakko; Ruokolainen, Janne; Alexandridis, Paschalis; Iatrou, Hermis
Abstract A facile strategy is developed to synthesize Au nanoparticles (Au‐NPs) using water‐soluble poly(L‐proline) (PLP). The synthesized NPs were characterized by TEM, FTIR and NMR spectroscopy, thermogravimetric analysis, and circular dichroism. It was found that PLP has a "dual" role as an efficient reductant of Au(III) and simultaneously as a stabilizing agent of Au‐NPs. The influence of PLP molecular weight, temperature, initial Au(III) concentration, and Au(III)/PLP molar ratio on the size and dispersity of Au‐NPs is examined. It was found that the unique extended secondary structure of PLP II resulted in the facile formation of highly crystalline Au‐NPs in water at a very low Au(III)/PLP molar ratio. These Au‐NPs have the smallest dimensions and size distributions among NPs synthesized so far by polymeric materials in aqueous media, and exhibit enduring colloidal stability. Therefore, by utilizing biocompatible and benign materials in water, we managed to obtain Au‐NPs, so as the final product is ready‐to‐use for biomedical applications. © 2013 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013